Geopolitical Conflict and Economic Performance: Evidance from the Israel-Palestine Conflict in the MENA Region - Zedriansyah .; Arivina Ratih; Ambya . (CV. ITTC INDONESIA, 2026)
Geopolitical conflict is considered an external shock that can disrupt regional economic stability through its impact on trade and economic growth. The prolonged Israel–Palestine conflict has created spillover effects across the Middle East and North Africa (MENA) region, affecting macroeconomic performance. This study aims to analyze the impact of the Israel–Palestine conflict on trade openness and economic growth (GDP) in the MENA region during the period 2010–2024. This research uses a quantitative approach with panel data analysis. The population consists of countries in the MENA region, with selected samples based on data availability. Secondary data are obtained from international institutions such as the World Bank. The analysis employs panel data regression using the Fixed Effect Model (FEM), selected based on the Chow and Hausman tests. The study also includes GDP per capita, inflation, investment, and global oil prices as control variables. The results show that the Israel–Palestine conflict has a negative effect on trade openness and economic growth. Trade openness, GDP per capita, and investment have positive effects, while inflation has a negative impact. Global oil prices significantly influence economic performance. These findings imply the importance of strengthening economic resilience and adaptive policies to mitigate the effects of geopolitical instability in the MENA region.